Análise geomorfológica e ambiental do município de Tatuí - Machado Junior, Claudio Machado (Universidade Federal de São Carlos, 2021)
The work developed refers to a research of environmental geomorphology and was based on the geomorphological characterization of the municipality of Tatuí, located in the SE portion of the state of São Paulo, Brazil. Besides the geomorphological analysis, developed from the identification of patterns of relief forms, the research also addressed the main environmental impacts that occur in the municipality. The methodology used in the work was based on theoretical references of Geomorphology, dealing with the taxonomic classification and the levels of approach of the relief. There was a bibliographic review of the theme, the elaboration of thematic maps, and field work. As a result, it was found that the municipality has six relief units, whose diverse characteristics are related to the different rocks found in its territory. Besides this, the lithological contacts themselves impose constraints on the area's drainage network, establishing different levels of dissection. Structural aspects such as faults and diabase dikes also influence the regional relief, and consequently, the landscape of the municipality. Allied to these characteristics, different activities related to land use were observed in the territory of Tatuí, focusing on elements related to the urban area, the impact of sealing and surface runoff in the city, which often presents flooding events and collapse of river slopes. A discussion on mining activity is also addressed in the work, in view of its expressiveness in the local economy. This end-of-course paper thus contemplates the results expected by the project and certainly constitutes a base from which future, more specific, studies can be unfolded.
Geomorphological and environmental analysis of the municipality of Tatuí
Keywords: Geomorfologia ambiental; Tatuí; Unidades do relevo; Análise ambiental; Ações antrópicas; Paisagem; Environmental geomorphology; Topographic units; Environmental analysis; Human activities; Landscape; CIENCIAS HUMANAS::GEOGRAFIA; 15. Vida Terrestre; 6. Água Potável e Saneamento; 10. Redução das Desigualdades